An In-Depth Look at the Discussion on the Medium of Education - Arkin, Erkan; Osam, Necdet (Ahmet Yesevi Univ, 2014)
This research investigated, through an exploratory case study, the impact of English-medium instruction (EMI) on disciplinary learning in a Turkish university context. A survey given out to undergraduate university students studying at an English-medium university showed that while EMI is perceived as necessary for professional and academic career prospects, the process of disciplinary learning is perceived to be negatively affected due to the limited language skills of the students. The researchers then decided to investigate the issue in more depth through a case study which included videotaped classroom observations and follow up interviews with the participating students, using stimulated recall. The results revealed that the students in the observed lectures had problems following the lecture and comprehending the content due to limited language skills. Based on the findings, this research proposes practical implications for a more effective addressing of both the language and content needs of learners studying at an EMI context.
Keywords: Higher education; English-Medium Instruction (EMI); language of instruction; disciplinary learning